PELAKSANAAN PROGRAM BIMBINGAN DAN KONSELING DALAM MENCAPAI KEMATANGAN KARIER SISWA KELAS XII DI SMK NEGERI 1 BOYOLANGU TULUNGAGUNG - Winarsih Winarsih; Moh. Gufron (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
The existence of Guidance and Counseling services has strong legality and has become an integrated part of the national education system with the explicit recognition of the title of counselor in Law no. 20/2003 on the National Education System. Recognition of the legality of the counselor profession is in line with the paradigm of thinking that contains the concept of redefining education and the prepositions of guidance and counseling. Guidance is the process of providing assistance to individuals that is carried out continuously, so that the individual can understand himself, so that he is able to direct himself and can act naturally, in accordance with the demands and circumstances of the family and society. Career guidance is an activity and assistance service to students with the aim that they gain an understanding of the world of work as well as a guide on how to achieve it. In the context of implementing career guidance services in schools, every educator is required to understand deeply and thoroughly about the basics or main ideas that underlie the implementation of career guidance in schools. With this understanding, educators are expected to be able to strengthen confidence and a greater sense of responsibility. In general, the purpose of career guidance in schools is to assist students in understanding themselves and their environment, in making decisions, planning, and directing activities that lead to careers and ways of life that will give a sense of satisfaction according to, in harmony, and balance with themselves and their environment. In order for career guidance in schools to function properly in accordance with the goals that have been set, a supervisor or school counselor needs to pay attention to the principles of career guidance in schools, especially in the preparation of program implementation services.